Trauma care in China: a systematic review - Zhang, Zhongheng; Hong, Yucai; Gregory, James S. (Journal of Emergency and Critical Care Medicine; Vol 1 (November 2017): Journal of Emergency and Critical Care Medicine, 2017)
The country of China has one of the largest populations in the world. It has experienced a logarithmic growth in population and economy over the last 20 years. This has put a spot light on the delivery of health care and stressed the need for development of an organized systematic approach to trauma care. Adoption of western approaches to trauma care requires modification to fit the uniqueness of China. Most western systems of care have been in a continuous process of development and refinement since the end of World War II [1945] and trauma systems in particular since 1971. China has not had this benefit and this paper will point to the areas of success and suggestions for continued progress and improvement.